The Enneads of Plotinus. a commentary - Kalligas, Paul (Princeton University Press, 2014)
This is the first volume of a groundbreaking commentary on one of the most important works of ancient philosophy, the Enneads of Plotinus-a text that formed the basis of Neoplatonism and had a deep influence on early Christian thought and medieval and Renaissance philosophy. This volume covers the first three of the six Enneads, as well as Porphyry's Life of Plotinus, a document in which Plotinus's student-the collector and arranger of the Enneads-introduces the philosopher and his work. A landmark contribution to modern Plotinus scholarship, Paul Kalligas's commentary is the most detailed an.